Bio-electrolysis contribute to simultaneous bio-hydrogen recovery and phosphorus release from waste activated sludge assisted with prefermentation. (15th October 2019) - Zhou, Aijuan; Liu, Zhihong; Wang, Sufang; Chen, E.; Wei, Yaoli; Liu, Wenzong; Wang, Aijie; Yue, Xiuping
Abstract: Waste activated sludge (WAS) is a promising phosphorus (P) source for fertilizer production; however, it is mainly enmeshed inside microbial cells or extracellular polymeric matrixes. Thus, efficient P release is a key goal. This study provided an effective route to simultaneously release organic P (OP) and harvest hydrogen from WAS via bio-electrolysis assisted with prefermentation system (AD_MEC). The clarification of P fractions in both solid and liquid phases and the underlying mechanism in this cascading system were explored. Free nitrous acid (FNA) was employed to enhance WAS hydrolysis. The results showed that hydrogen generation was effectively accelerated: 0.54 mL per gram sludge (in volatile suspended solids (VSS)) was produced from raw WAS (AD_MEC_RWAS), which increased to 1.27 mL/g VSS from FNA-pretreated WAS (AD_MEC_FWAS). The limited OP release by prefermentation was enhanced via MECs; additionally, it was further promoted by FNA, and the treatment time was also shortened. The maximum OP release efficiency reached 54.6% at 112 h (AD_MEC_FWAS). Additionally, non-apatite and inorganic apatite P may regenerate in MECs due to the localized decrease in pH caused by hydrogen generation. This work may provide a scientific basis to enhance P and hydrogen co-recovery from WAS in forthcoming implementation. Graphical abstract: Image 1 Highlights: H2 recovery and P release from WAS was achieved in cascading conversion system. The limited OP release in prefermentation was accelerated via bio-electrolysis. FNA played a positive effect on H2 recovery and OP release from WAS. Underlying mechanism of cascading conversion system for P release was explored.